Land border areas between development requirements and customs zone restrictions - Abdelouahab, Chergui (The International tax journal, 2025)
The conceptual framework of the customs zone, the laws and regulations that control it, the characteristics of border regions, and the development elements they have will all be covered in this study. We will also discuss the special procedures and authority given to customs officers in this area, the implications of these authorities within the land area's customs zone, and the limitations placed on bringing about real development in these regions.